Representasi GoFood Sebagai Pengganti Ibu dalam Iklan “Ungkapkan yang di Hati, Kirimkan yang Berarti” - Nathania Raissa Gunawan; Guruh Ramdani; Mulyono (Unitri Press, 2026)
Advertisement, as a form of visual and verbal communication, utilizes various elements to attract attention and shape consumer understanding in accordance with its communicative goals. One advertisement that employs connotative signs to shape audience perception is GoFood’s “Ungkapkan yang Di Hati, Kirimkan yang Berarti” campaign. This ad goes beyond merely promoting a food delivery service; it also represents emotional values such as love and care, which are conveyed through its messaging. This study aims to analyze how GoFood is represented as a substitute for the role of a mother in the “Ungkapkan yang Di Hati, Kirimkan yang Berarti” advertisement. The research is conducted using a qualitative descriptive method, employing Stuart Hall’s theory of representation and Roland Barthes’ theory of extended connotation semiotics to uncover the connotative meanings and myths contained in the advertisement. This study is expected to contribute to a deeper understanding of how advertisements work through various connotative signs, visual, verbal, and textual, which can serve as creative methods during the advertisement production process. Abstrak Iklan sebagai bentuk komunikasi visual dan verbal memanfaatkan berbagai elemen untuk menarik perhatian dan membentuk pemahaman konsumen yang sesuai dengan tujuan komunikatifnya. Salah satu iklan yang juga memanfaatkan penanda-penanda konotatif yang membentuk presepsi audiens adalah iklan GoFood versi